Can the modeling for simplification of a dental implant surface affect the accuracy of 3D finite element analysis? - Verri, Fellippo Ramos [UNESP]; Cruz, Ronaldo Silva [UNESP]; de Souza Batista, Victor Eduardo [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Verri, Ana Caroline Gonçales [UNESP]; Lemos, Cleidiel Aparecido de Araújo [UNESP]; Santiago Júnior, Joel Ferreira; Pellizzer, Eduardo Piza [UNESP] (Taylor & Francis, 2016)
The aim of this study was to assess stress/strain of different implant modeling simplifications by 3D-FEA. Three variation of external hexagon implant (Ã 3.75 Ã 10Â mm) supporting one molar crown were simulated: A (no threads); B (slightly threads simplification); C (original design). 200Â N (axial) and 100Â N (oblique) were applied. Cortical bone was evaluated by maximum principal stress and microstrain qualitatively and quantitatively (ANOVA and Tukey post hoc (pÂ <Â 0.05)). Higher stress levels (pÂ <Â 0.05) were observed in model A. Models B and C presented similar stress transmission. It was possible to conclude that slightly simplification should be used for studies evaluating stress transferring for bone tissue.
Keywords: biomechanics; Dental implants; finite element analysis